Voltammetric study of the partitioning of macrolide antibiotics at the water/nitrobenzene interface. Relationship to the pharmacokinetic profiling of macrolides - Zoran Mandic (International Association of Physical Chemists (IAPC), 2014)
The ion transfer of a series of ionised 14- and 15-membered macrolide compounds across polarised water/nitrobenzene have been studied by cyclic voltammetry. Fourteen-membered macrolides transfer as singly-charged molecules in the wide pH range, while 15-membered macrolides can transfer as both singly and doubly protonated cations, depending on the pH of the aqueous solution. The results showed that the formal transfer potentials (  ) of the investigated compounds varied to a great extent and that minor changes in macrolide structure caused significant change in the corresponding formal transfer potentials. Among the investigated macrolides, azithromycin had the lowest formal transfer potential and its peculiar ADME behaviour is ascribed to this specific property.